How we Provide Nutritional Treatment in Hospitalized Patients? - Kelleci Cakir, Burcu; Balci, Cafer; Esme, Mert; Demirkan, Kutay; Halil, Meltem; Abbasoglu, Osman (Turkish Journal of Gastroenterology, 2021)
Background: In this study, we aimed to evaluate enteral nutrition (EN), parenteral nutrition (PN) and supplemental parenteral nutrition (SPN) in terms of achieving nutritional goals. Methods: Patients receiving either EN, PN, or SPN treatment followed up by the clinical nutrition team between January and December 2017 at the university research and training hospital were included in the study. Daily nutritional requirements were calculated according to the recommendations. Total energy intake during nutritional treatment (NT) and all metabolic, mechanical, technical complications of NT were recorded. Results: A total of 603 inpatients were included in the study. The nutritional goal was achieved in the majority of the SPN group patients (87.5%) statistically significant relation was found between the achievement of the target (or not) and PN access route (peripheral or central) (P < .001). However, none of the complications found statistically related to achieving the target, including gastrointestinal complications of EN (P = .46), metabolic complications of EN (P = .07), mechanical complications of EN (P = .79), metabolic complications of PN (P = .89), gastrointestinal complications in SPN group (P = .45), and metabolic complications in SPN group (P = .68). Conclusion: Nutritional goals could be achieved with SPN without increasing complications in the majority of patients. Commencement of SPN should be considered for positive outcomes in patients who failed to achieve desired nutritional outcomes.